Upregulation of expression of the chemokine receptor CCR5 by hydrogen peroxide in human monocytes. - Lehoux, Geneviève (2003)
The objective of this study was to test the hypothesis that an oxidative stress can serve as a signal to regulate the expression of CCR5. When human monocytes were exposed to graded concentration of hydrogen peroxide (H(2)O(2)), CCR5 mRNA levels increased maximally at 4 h of exposure to 200 microM of H(2)O(2) and decreased by 24 h of treatment. Pretreatment of monocytes with the NF-kappaB inhibitor BAY 11-8072 blocked the H(2)O(2)-induced augmentation of CCR5 mRNA expression, suggesting a role for this transcription factor in the regulation of CCR5 expression. CCR5 protein expression on the plasma membrane was also increased by treatment with H(2)O(2,) as assessed by flow cytometry. This was accompanied by enhanced responsiveness of H(2)O(2)-pretreated monocytes to the CCR5 ligand MIP-1beta in terms of chemotaxis and c-fos gene activation. Our results suggest that oxidative stress may indeed modulate the expression of chemokine receptors and thus contribute to regulation of the inflammatory process.